Performing rustics: pastoral moments and masques in Henry Purcell’s King Arthur (1691) and Benjamin Britten’s Gloriana (1953) - Catherine HOFFMANN (E-REA)
This essay analyses the functions and forms of the pastoral masques in two musical works celebrating England and its monarchs: Purcell’s semi-opera King Arthur (1691) and Britten’s coronation opera Gloriana (1953). The conventions of the masque and the pastoral combine in performances involving singing and dancing by rustics and shepherds. In both works, the pastoral masques or moments are spectacles within the spectacle, offered as gifts to the character(s) on stage. The masques thus foreground the artificiality of pastoral by this mise-en-abyme of the pageantry attending royal occasions. They invite reflection on the relation between the pastoral texts and their musical settings, and raise the question of what constitutes “pastoral” music. Given the themes and original functions of the two works and the national status of their composers, the essay also examines the nature of the “Englishness” of the pastoral masques in King Arthur and Gloriana.